Organizational Cynicism and Job Satisfaction among Air Traffic Controllers: The Roles of Spiritual Organization, Organizational Commitment, and Turnover Intention - Mochamad Soelton; Janet Apta Adristy; Arif Zulkarnain; Subur Karyatun; Yanto Ramli; Irfan Noviandy Aulia; Mohammed Hokroh (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Air Traffic Controllers (ATCs) occupy one of the most critical roles in the aviation industry, characterized by high work pressure, intense responsibility, and zero-tolerance for error. Such demanding conditions may foster organizational cynicism, which can undermine employees’ psychological well-being, job satisfaction, and intention to remain with the organization.Purpose: This study aims to examine the direct and indirect effects of organizational cynicism on job satisfaction, as well as the mediating roles of Spiritual Organization and organizational commitment, and the moderating role of turnover intention among ATC employees.Design/methodology/approach: This study employs a quantitative approach using a survey method. The sample comprises the entire population of Air Traffic Controller employees at Soekarno–Hatta International Airport, totaling 129 respondents. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM).Findings/Results: The results indicate that organizational cynicism has a significant negative effect on job satisfaction. However, Spiritual Organization and organizational commitment are found to play important roles in mitigating this negative effect. Strengthening spiritual values within the organization and fostering employee commitment contribute to higher levels of job satisfaction and reduce the detrimental impact of cynicism.Conclusion: Organizations, particularly those operating in high-risk and high-pressure environments such as air traffic control services, need to proactively reduce organizational cynicism by enhancing transparency, fairness, and effective communication. These efforts are essential to improve employee job satisfaction and organizational sustainability.Originality/value (State of the art): This study extends the existing literature by integrating Spiritual Organization as a mediating variable and organizational commitment as a moderating mechanism in the relationship between organizational cynicism and job satisfaction. The findings highlight the complex psychological dynamics in safety-critical organizations and offer a more comprehensive understanding of employee attitudes in the aviation navigation context. Keywords: air traffic controller, organizational cynicism, spiritual organization, organizational commitment, turn over intention